Risk factors associated with prevalence of breast cancer in a gyneco-obstetric hospital - Cruz Hernandez, Montserrat (2023)
Objective: To explain the association between risk factors and the prevalence of breast cancer in women in a gynecological-obstetric hospital. Methodology: quantitative, predictive, non-experimental, cross-sectional and retrospective study. Two groups of women with and without a diagnosis of breast cancer between 20 and 70 years old were carried out during 2015-2020. Result: 284 files of women were studied, 136 formed GCC and 148 G-SC, with a median age of 50.5 and 43.1 years, respectively. The risk factors associated with the development of breast cancer were age (OR 0.946, CI 95% 0.920-0.973 p = 0.000), family history of CAMA (OR 0.275, CI% 95% 0.837-1.126 p = 0.000) and consumption of alcohol (OR 4.151, CI 95% 1.772-9.725 p = 0.001). Conclusión: The prevalence of breast cancer is associated with non-modifiable risk factors such as: older women and family history of breast cancer. Other non-modifiable risk factors such as alcohol consumption are associated with an increase in suffering from this neoplasm.